Peran Pendidikan Islam dalam Mendorong Kemajuan Sains dan Teknologi (IPTEK) di Era Globalisasi - Putri Nurafifah; Puti Rasina Mianti; Nayla Nur Zahrania; Abdul Azis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to examine the role of Islamic education in encouraging the advancement of science and technology (science and technology) in the era of globalization. In facing the challenges of digitalization and value degradation, Islamic education is expected to be able to integrate Islamic values with technological developments harmoniously. The research method used is library research through analyzing various relevant literature sources. Data collection is done by tracing and analyzing various literatures, including books, scientific journals, and policy documents relevant to the theme of Islamic education. In addition, researchers also use qualitative techniques in analyzing data, which will then be presented descriptively. The results of the study show that Islamic education has great potential in forming a generation that is not only superior in science and technology, but also has good morals. The strategies highlighted include increasing the digital competence of educators, strengthening Islamic digital literacy, developing Islamic digital content, innovating learning methods, and integrating digital ethics in the curriculum. This research confirms that Islamic education is not an obstacle to technological progress, but a strategic partner in creating a modern civilization based on spiritual and moral values.